Perception of Hydro-meteorological hazard in Camagüey province: a starting point for environmental education - Parrado Álvarez , Oscar; Cardoso Hurtado , Tania; Dora E. Francis Archer , Dora E. Francis Archer (Transformación, 2024)
The results of the study of the perception of hazard due to floods, intense rains, in-land sea floods and strong winds are presented, according to the methodology proposed by the National Group of Evaluation of Risks that coordinates by the Environment Agency (AMA) of the CITMA.  The analysis units were the municipalities and the d areas of defense. For the statistical analysis of data the software Excel, SPSS and Data Entry were used. The sample taken includes 1 599 people which represents 0, 20% of the population of the county; 62.3% of the sample belongs to the municipalities of Camagüey, Florida, Nuevitas, Vertientes and Santa Cruz del Sur. The results of surveys, in most of those interviewed (53%), determines that the level of perception of the hazard on the part of the population is mainly medium (perception closed to reality) aside from the structural, functional, economic and ecological vulnerabilities. There are differences levels of perception form one Popular Council to another. These differences are discussed according to the studied socio demographics variables and the hints given for the needed environmental education.
Keywords: Environmental perceptions; environmental education; hydro-meteorological hazard; social vulnerability